2004
DOI: 10.1002/pssb.200304513
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the magnetic moment enhancement of the ordered Fe50Co50 alloys

Abstract: PACS 75.50.Bb We investigated the physical origin of the magnetic moment enhancements of the ordered Fe 50 Co 50 alloys with B2 and L1 0 structures by using the all-electron total-energy full-potential linearized augmented plane wave (FLAPW) method within the generalized gradient approximation. Pure Fe and Co with the WignerSeitz radii taken from the alloys are also calculated for comparsion. It is confirmed that the magnetic moments of Fe in the alloys are enhanced significantly, while those of Co remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the Co-Si disordered system, when a Co was swapped by a nearest-neighbouring Si, the disordered Co has seven Co and one Si as the 1nn, which is similar to that of the bcc Co where the Co has eight Co atoms as the 1nn. Indeed, the magnetic moment of disordered Co atom is close to that (1.81 µ B ) of the bcc Co. [26] The study of effect of disorder on the half-metallic character of Co 2 MnSi is also suggested that the 1nn mainly dictates the behaviour of the magnetic moments of transition metals. [15] For the Fe-Si disorder, the local magnetic moments of the Co and Fe atoms are affected very little, and the total magnetic moment remains at an integer value of 6.00 µ B , as in the ordered system, thus, we can expect that the Co 2 FeSi keeps its halfmetallicity against this kind of disorder.…”
Section: Resultsmentioning
confidence: 91%
“…In the Co-Si disordered system, when a Co was swapped by a nearest-neighbouring Si, the disordered Co has seven Co and one Si as the 1nn, which is similar to that of the bcc Co where the Co has eight Co atoms as the 1nn. Indeed, the magnetic moment of disordered Co atom is close to that (1.81 µ B ) of the bcc Co. [26] The study of effect of disorder on the half-metallic character of Co 2 MnSi is also suggested that the 1nn mainly dictates the behaviour of the magnetic moments of transition metals. [15] For the Fe-Si disorder, the local magnetic moments of the Co and Fe atoms are affected very little, and the total magnetic moment remains at an integer value of 6.00 µ B , as in the ordered system, thus, we can expect that the Co 2 FeSi keeps its halfmetallicity against this kind of disorder.…”
Section: Resultsmentioning
confidence: 91%